The Influence of School Library Utilization and Reading Interest on Student Achievement - Shintia, Dheby; Arafat, Yasir; Setiawan, Andi Arif (Journal of Social Work and Science Education, 2021)
This study aimed at determining influence of using the school library and reading interest on student achievement fourth grade students of SD 04 OKU partially and simultaneously. This is a quantitative research with sampling using all class IV totaling 105 students. The variabels studied were the use of the school library (X1), reading interest (X2) and learning achievement (Y). Methods of data collection using a questionnaire. Data analysis using validity and reliability tests using the SPSS 22 for windows program. The results showed that there was an influence between the influences of the use of the school library on student achievement. This paper recommends to more focus on library and reading interest of students where school would have good students’ achievement.